2015
DOI: 10.1007/s12105-015-0664-7
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Triple Primary Head and Neck Malignancies: A Rare Case Report

Abstract: The occurrences of multiple primary malignant tumours in the head and neck region are reported as simultaneous, synchronous, or metachronous based on their chronology of presentation. Lymphoid malignancies presenting in association with squamous cell carcinoma in the head and neck region are extremely rare. We report a case of a 71 year old male patient with simultaneous triple primary malignancies of different histologic origin, involving larynx (squamous cell carcinoma), thyroid (papillary thyroid carcinoma)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…[ 2 ] We found only 2 reports in the English literature reporting simultaneous DTC and NHL. Rizkallah et al [ 3 ] reported similar case, whereas Singh et al [ 4 ] published recently a case with triple malignancies—laringeal cancer, DTC, and NHL. Although it is different from our case, Guzzo et al [ 5 ] reported 33 cases with synchronous DTC and squamous cell carcinoma of head and neck for the period 1975 to 2004, of which 31 were diagnosed during the pathological examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] We found only 2 reports in the English literature reporting simultaneous DTC and NHL. Rizkallah et al [ 3 ] reported similar case, whereas Singh et al [ 4 ] published recently a case with triple malignancies—laringeal cancer, DTC, and NHL. Although it is different from our case, Guzzo et al [ 5 ] reported 33 cases with synchronous DTC and squamous cell carcinoma of head and neck for the period 1975 to 2004, of which 31 were diagnosed during the pathological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the classic approach “solid cancer first,” due to the relatively good prognosis of PTC [ 4 ] and the advanced stage of NHL with a pronounced clinical manifestation and aggressive course, we first started the chemotherapy of NHL similar to other authors. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…Cancer that occurs within a year after another cancer was detected is defined as simultaneous cancer, and cancer occurring after 1 year of another is defined as heterochronous cancer; our study adopted this definition. There are some reports of simultaneous multiple primary cancers (15,16). In this study, the rate of simultaneous multiple primary cancers was 28.6% and the rate of heterochronous multiple primary cancers was 71.4%.…”
Section: Discussionmentioning
confidence: 52%
“…The prognosis of MPNs is better than that of recurrent and metastatic cancers [16]. In summary, to our knowledge, simultaneous triple primary neoplasms have an extremely low occurrence [17]. The exact etiology of MPNs is still unknown and we suspect that in this case, a diet high in salty and pickled foods was a major contributing factor.…”
Section: Discussionmentioning
confidence: 91%